Blind watermark detection based on K‐S test in radio‐frequency signals. Issue 1 (1st January 2020) - Xie, Xu; Xu, Zhengguang
Abstract : Radio‐frequency (RF) watermarking is a new technology for physical layer authentication, whose carrier is not the traditional multimedia signals but the digital signals. In the available literature, the watermark detectors are based on the cooperative environment, where the parameters of the watermark signal are known to the receiver. In this Letter, a blind watermark detection scheme with Kolmogorov–Smirnov (K‐S) test is presented. The simulation results show that the proposed scheme is effective.